Real-world experience with the cusp-overlap deployment technique in transcatheter aortic valve replacement: A propensity-matched analysis - Maier, Oliver; Piayda, Kerstin; Binnebößel, Stephan; Berisha, Nora; Afzal, Shazia; Polzin, Amin; Klein, Kathrin; Westenfeld, Ralf; Horn, Patrick; Jung, Christian; Kelm, Malte; Veulemans, Verena; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The implantation depth (ID) is a critical condition for optimal hemodynamic and clinical outcomes in transcatheter aortic valve replacement (TAVR). The recently recommended cusp-overlap technique (COT) offers optimized fluoroscopic projections facilitating a precise ID. This single-center observational study aimed to investigate short-term clinical performance, safety, and efficacy outcomes in patients undergoing TAVR with self-expandable prostheses and application of COT in a real-world setting. Methods: From September 2020 to April 2021, a total of 170 patients underwent TAVR with self-expandable devices and the application of COT, while 589 patients were treated from January 2016 to August 2020 with a conventional three-cusp coplanar view approach. The final ID and thirty-day outcomes were compared after 1:1 propensity score matching, resulting in 150 patients in both cohorts. Results: The mean ID was significantly reduced in the COT cohort (-4.2±2.7 vs. -4.9±2.3 mm; p=0.007) with an improvement of ID symmetry of less than 2 mm difference below the annular plane (47.3% vs. 57.3%; p=0.083). The rate of new permanent pacemaker implantation (PPI) following TAVR was effectively reduced (8.0% vs. 16.8%; p=0.028). While the fluoroscopy time decreased (18.4±7.6 vs. 19.8±7.6 min; p=0.023), the dose area product increased in the COT group (4951±3662 vs. 3875±2775 Gy*cm2; p=0.005). Patients implanted with COT had a shorter length of in-hospital stay (8.4±4.0 vs. 10.3±6.7 days; p=0.007). Conclusions: TAVR using the cusp-overlap deployment technique is associated with an optimized implantation depth, leading to fewer permanent conduction disturbances. However, our in-depth analysis showed for the first time an increase of radiation dose due to extreme angulations of the gantry to obtain the cusp-overlap view.